Assessment of a novel equine tarsocrural experimental joint disease model using recombinant interleukin-1β and arthroscopic articular sampling of the medial malleolus of the tibia on the standing sedated horse. (November 2017) - Nelson, B.B.; King, M.R.; Frisbie, D.D.
Highlights: An equine tarsocrural joint synovitis model induced lameness and synovial effusion replicative of clinical disease. This minimally invasive surgical technique provided sufficient cartilage and synovium for laboratory assays. Using sedation and local anesthetic techniques, the surgical procedure could be performed standing and was well tolerated. No incisional or lameness complications were observed after the technique was used. This surgical technique facilitated joint tissue collection while preventing the need for general anesthesia or euthanasia. Abstract: Joint disease and osteoarthritis are common problems in the horse and numerous experimental studies have been developed to determine the safety and efficacy of new therapies. Synovitis, a critical component of joint disease, has been experimentally induced using recombinant interleukin-1 beta (reIL-1β) to investigate new joint therapies in a controlled environment, although the use of reIL-1β has not been reported in the equine tarsocrural joint. A common consequence of performing controlled experiments is that articular tissue collection typically requires general anesthesia or euthanasia. This report describes a minimally invasive surgical biopsy technique to harvest joint tissues from the tarsocrural joint in standing horses. The aims of the study were to assess subjective and objective pain parameters following reIL-1β induced synovitis in the tarsocrural joint and to describe the surgical technique including the location and quantity of tissues obtained with this method. Experimental synovitis was induced using reIL-1β in one equine tarsocrural joint of each horse using a randomised controlled design. The minimally invasive surgical technique provided sufficient amounts of articular cartilage from the medial malleolus of the tibia and synovium to perform viability, biochemical and histological assessments without necessitating general anesthesia. The minimally invasive technique also allowed for lameness assessment that could have been influenced by more invasive methods of tissue collection. No incisional or lameness complications were detected after use. The synovitis model and surgical technique provided ample tissue for laboratory evaluation and avoided general anesthesia or sacrifice of the horse.